Photonics-based modular multistate digital coherent system - I. V. Unchenko; A. A. Emelyanov (Российский технологический журнал)
Objectives. The study aimed to develop interspecies and interclass methods for constructing coherent radio engineering systems based on a modular complementary structure.Methods. A set of modules and submodules having no narrow specialization and together constituting a flexible broadband hardware-reconfigurable software-defined radio engineering structure is considered as the basic set for constructing a digital radio photonic system path. Due to their broadbandness and complementary structure, modules and submodules have many applications both as self-sustained devices and as part of more complex systems.Results. Functional diagrams of modern digital receiver-shapers, as well as modules for amplifying radio frequency signals and converting radio frequency signals into an optical signal are presented along with a radio photonic synchronization network for generating clock signals. Calculations of the introduced phase error of a quartz singlemode fiber and graphs of the dependence of the change in the signal phase on external influencing factors are given. A concept for integrating the presented modules into the construction of a modular transceiver multiposition wideband coherent digital radio photonic system is proposed. The results of calculating radiation patterns and mathematical modeling the beam deflection of a broadband antenna array are presented along with antenna systems based thereon.Conclusions. The proposed circuit design solutions allow the time required for developing new types of systems to be significantly reduced due to the range of ready-made technical solutions. Not only are the parameters of the developed devices comparable to the best world analogues, but they also surpass existing solutions in terms of system integration. The developments have been tested under R&D project at the Kaluga Scientific Research Institute of Radio Technology and Hardware Solution Technologies (TAR). The proposed solutions are integrated at the subsystem level into advanced developments of products for civil and special purpose. Further development of the concept of building ultra-wideband devices allows reaching a new level in the technology of constructing modular multiposition coherent digital radio photonic systems.